Pengaruh Perilaku Belajar, Kecerdasan Emosional dan Kecerdasan Adversitas pada Tingkat Pemahaman Akuntansi - Suwi Novita Devi, Made; Sujana, I Ketut; Pradnyantha Wirasedana, I Wayan (E-Jurnal Akuntansi, 2020)
This study aims to determine the effect of learning behavior, emotional intelligence and adversity intelligence on the levels of understanding accounting. The study was conducted on students of the S1 Accounting Study Program at 2016 Regular Bukit Class. This study uses 142 people for sample, by used a purposive sampling technique. The analysis technique used Multiple Linear Regression Analysis.The results found that learning behavior had no effect on the levels of understanding accounting. Meanwhile, emotional intelligence and adversity intelligence have a positive effect on the levels of understanding accounting. Keywords: Levels Of Understanding Accounting; Learning Behavior; Emotional Intelligence; Adversity Intelligence.